2021
DOI: 10.7759/cureus.16763
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Intervention to Help Improve Motor Function in Patients Undergoing Rehabilitation for Cerebral Palsy, Parkinson’s Disease, or Stroke: A Systematic Review of Randomized Controlled Trials

Abstract: There are many successful interventions in medicine, especially in neurology and rehabilitation. The neurosciences represent an area of medicine with tremendous recent research innovations, one of which is virtual reality. This paper aims to discover the powerful relationship between virtual reality and rehabilitation. We assessed the effectiveness of virtual reality-based rehabilitation compared to conventional rehabilitation on motor function recovery of three patient groups: patients with a diagnosis of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…8,9 Several previous reviews did not examine the role of virtual reality in participation. [10][11][12][13][64][65][66] We did not observe significant enhancement on either the amount of use or the quality of movement in virtual reality group comparing with the control group. Programs used in the included studies mainly focused on inducing goal-oriented task-specific motions.…”
Section: Discussioncontrasting
confidence: 62%
“…8,9 Several previous reviews did not examine the role of virtual reality in participation. [10][11][12][13][64][65][66] We did not observe significant enhancement on either the amount of use or the quality of movement in virtual reality group comparing with the control group. Programs used in the included studies mainly focused on inducing goal-oriented task-specific motions.…”
Section: Discussioncontrasting
confidence: 62%
“…This reduces the fear of falling, and transfers this confidence into the real world through motor learning [ 51 ]. Amirthalingam et al [ 52 ] recently suggested that task repetition using VR increases neural plasticity in both post-stroke patients and patients diagnosed with Parkinson’s disease…”
Section: Discussionmentioning
confidence: 99%
“…The application of VR is not limited to these education or training purposes but is increasingly being used for therapeutic purposes as well. Several major therapeutic purposes of VR use include distraction from pain or uncomfortable medical procedures [ 2 , 11 ], relaxation and mindfulness for stress and symptom improvement [ 12 - 15 ], cognitive coping as psychotherapy [ 16 , 17 ], and rehabilitation of neuromotor functions [ 18 ]. VR has shown promising levels of effectiveness in various clinical scenarios.…”
Section: Virtual Reality In Health Carementioning
confidence: 99%
“…In recent years, VR has shown its potential as an assistive technology to aid the rehabilitation of patients with impaired neuromotor functions. Although VR cannot replace conventional physical or occupational therapies, it can promote the effectiveness of rehabilitation by providing task-oriented and multisensory training within an individualized safe virtual environment [ 18 ]. Mekbib et al [ 24 ] developed a VR-based rehabilitation system and validated its therapeutic potential in 23 recent patients who had stroke.…”
Section: Virtual Reality In Health Carementioning
confidence: 99%
See 1 more Smart Citation